Influence of Internal Marketing on Marketing Performance with Branding Strategy in PT. Jayaland Sidoarjo - Fabian Farandori; Muhadjir Anwar (LPPM of NAROTAMA UNIVERSITY, 2021)
JAYALAND is a developer of the Puri Surya Jaya Gedangan Housing in Sidoarjo. Observing this business opportunity, the company has the opportunity to attract consumers' interest in purchasing housing products that have been built in the city of Sidoarjo. PT. Jayaland must understand the importance of marketing expenses and manage them to provide sustainable benefits for the company. The purposes of this study are 1) to find out and empirically test the influence of Internal Marketing on Marketing Performance at Puri Surya Jaya Housing PT. Jayaland Sidoarjo; 2) to find out and empirically test the impact of Internal Marketing on Marketing Performance with Branding Strategy as a moderating variable at Puri Surya Jaya Housing PT. Jayaland Sidoarjo. In this study, the sampling technique used a census where the sample members obtained were about 41 employees of the Puri Surya Jaya Housing Marketing Division PT. Jayaland Sidoarjo. The data analysis technique in this study used the Partial Least Square (PLS) method. This study concludes that Internal Marketing has a significant positive effect on marketing performance, and Branding Strategy as Moderating Variable has no impact on Marketing Performance.